2021
DOI: 10.35609/gcbssproceeding.2021.12(105)
|View full text |Cite
|
Sign up to set email alerts
|

Credit Risk Management for College Students: An Analysis of Influencing Factors Based on 5C Approach

Abstract: This paper focuses on the construction of college students' credit evaluation system and credit risk management under the background of big data. Firstly, based on the 5C approach, this paper evaluates the personal credit of college students from 5 dimensions and 24 indicators, which finally contribute to the establishment of the credit evaluation system for college students. Then, the partial least squares method is used to build the structural equation model to evaluate the effectiveness of the credit evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(2019) found that banking regulation mitigates the adverse impact of capital flow volatility on economic growth. Most Chinese scholars believe that the increase of capital inflow will promote economic growth (Cheng & Li, 2020; Zhou & Zhong, 2020; Zou, 2004). Another research focus area in China is the impact of regional capital flows on regional economic disparities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2019) found that banking regulation mitigates the adverse impact of capital flow volatility on economic growth. Most Chinese scholars believe that the increase of capital inflow will promote economic growth (Cheng & Li, 2020; Zhou & Zhong, 2020; Zou, 2004). Another research focus area in China is the impact of regional capital flows on regional economic disparities.…”
Section: Literature Reviewmentioning
confidence: 99%